Messages of Religious Moderation Education in Sambas Islamic Manuscripts - Mahrus, Erwin; Prasojo, Zaenuddin Hudi; Busro, Busro (Madania: Jurnal Kajian Keislaman, 2020)
In the beginning of the 20th century, West Kalimantan had a number of social issues, especially in the context of religious moderation. Both individuals and groups claim one another as being the most proper ones. Fom that condition, a negative impact occurred on social order in society. Observing to this situation, Muhammad Basiuni Imran, the Maharaja Imam to the Kingdom of Sambas, initiated a meeting of Islamic religious leaders and priests for the Western part of Borneo. This work is based on research conducted on manuscripts that recorded the speeches of West Kalimantan religious leaders and priests (ʻâlim ulamâ) in the meeting. Considering that this study is aimed at exploring the manuscripts, to approach the issue the authors employ philology that includes the inventory of manuscripts, identification of origins, compiling descriptions, making text summaries, and finally presenting messages of religious moderation education in the related texts. This study successfully concludes that those Islamic manuscripts of Sambas in West Kalimantan, including the manuscript by Maharaja Imam Sambas are on the end of extinction due to ages of century. The text is full of messages of religious moderation education as seen in the principle of flexibility and renewal (tajdîd), the principle of ease (taysîr), and the principle of tolerance (tasâmuh). Finally, the madrasa founded by Maharaja Imam Sambas is as among the oldest Islamic education institution that promotes religious moderation in West Kalimantan. Di awal abad ke-20, Kalimantan Barat mengalami berbagai isu sosial, khususnya yang berkaitan dengan masalah moderasi beragama. Setiap kelompok dan bahkan individu cenderung mengklaim kebenaran masing-masing dalam menyikapi kondisi soail yang ada dalam rangka parktik keberagamaan di Sambas. Kondisi tersebut telah berdampak negative pada keberlangsungan kehidupan sosial keagamaan dalam masyarakat. Menyikapi kondisi tersbut, Muhammad Basiuni Imron, Maharaja Imam Sambas, menginisiasi pertemuan yang mengundang para ulama dan tokoh agama Islam yang ada di wilayah Borneo bagian Barat kala itu. Artikel ini mengexplorasi hasil pertemuan tersebut yang terekam dalam kumpulan manuskrip Islam yang ditulis oleh Maharaja Imam Sambas tersebut. Oleh karena itu penulis menggunakan pendekatan filologi yang meliputi inventarisir manuskrip, identifikasi asal manuskrip, penyajian deskripsi isi manuskrip, membuat kesimpulan isi teks, dan penyajian pesan-pesan tentag Pendidikan moderasi beragama yang dikandungi oleh teks. Paper ini menyajikan kesimpulan bahwa kumpulan manuskrip Islam di Sambas tersebut yang juga termasuk yang ditulis oleh Maharaja Iman Sambas ialah tergolong manuskrip langka dan berada pada kondisi yang meprihatinkan. Kompulan manuskrip tersebut mengandung banyak pesan tentang pentingnya Pendidikan moderasi beragama yang terkandung pada beberapa prinsip seperti tajdîd, tasyîr, dan tasâmuh. Akhirnya, madrasah sebagai institusi pendidikan Islam yang didirikan oleh Maharaja Imam Sambas merupakan salah dari beberapa institusi pendidikan Islam yang menjadi bukti gerakan mempromosikan moderasi beragama Kalimantan Barat.